Internet Governance: a critical theory analysis of the Internet Corporation for Assigned Names and Numbers (ICANN) - Gomes Sequeiros, Felipe (Université d'Ottawa | University of Ottawa, 2021)
The Internet has expanded its reach worldwide and its importance to almost every aspect of contemporary life. Suffice it to say this trend is expected to continue its upward trajectory. The Internet Governance system was established in the late 1990s with distinct characteristics compared to other international management models. As Internet Governance gains more importance, this major research paper proposes to analyze the management of the Internet’s critical resources, more specifically the Internet Corporation for Assigned Names and Numbers (ICANN), the Californian non-profit company responsible for this task worldwide. ICANN’s creation, operationality, and contested legitimacy will be assessed, a topic that divides countries into separate poles: one side supporting the organization and the other claiming for comprehensive reforms in the system. This major research paper (MRP) shows how, as a reflection of their hegemonic power, the US and its allies mobilize a particular set of discourses centred on freedom to legitimize the current regime and de-legitimize calls for radical reforms. It will also analyze how the lack of comprehensive reforms has an impact on ICANN’s legitimacy. The MRP will employ insights drawn from critical International Relations (IR) theory and use data collected from ICANN’s Board of Directors, the decision-making body, to evaluate discourses and international representation, essential factors in assessing ICANN’s legitimacy in the global Internet Governance regime.